1991
DOI: 10.1088/0031-9155/36/11/006
|View full text |Cite
|
Sign up to set email alerts
|

Forces acting in the direction of propagation in pulsed ultrasound fields

Abstract: This paper considers some non-thermal effects resulting from absorption of acoustic energy from an ultrasound beam. An experimental investigation of the location of the 'source pump', responsible for the generation of streaming in high amplitude diagnostic fields in water, is reported. Acoustically transparent membranes were inserted in the ultrasound field in order to restrict the streaming volume. It is shown that the major contribution to an acoustic stream is generated in the region near to the focus of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 9 publications
0
49
0
Order By: Relevance
“…Convective acceleration ðu Á rÞu is potentially significant (compared to one-dimensional Eckart streaming). Starritt et al (1991) showed that even when controlling for acoustic intensity, nonlinear distortion in the acoustic wave can cause far larger acoustic streaming amplitudes, about a 1 order of magnitude increase due to the presence of harmonics and their consequent attenuation in the fluid.…”
Section: Coarse-grained (Multidimensional) Eckartmentioning
confidence: 99%
“…Convective acceleration ðu Á rÞu is potentially significant (compared to one-dimensional Eckart streaming). Starritt et al (1991) showed that even when controlling for acoustic intensity, nonlinear distortion in the acoustic wave can cause far larger acoustic streaming amplitudes, about a 1 order of magnitude increase due to the presence of harmonics and their consequent attenuation in the fluid.…”
Section: Coarse-grained (Multidimensional) Eckartmentioning
confidence: 99%
“…This group of imaging techniques is called elasticity imaging [28]. The general approach in elasticity imaging is to measure the response of tissue to an excitation force [29]. The excitation force used in current work is an acoustic pulse of specific frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Just pushing the bubbles against the cell repetitively, may be sufficient to stimulate cell uptake [24]. At high ultrasound pressures, bubbles have been shown to translate very rapidly in vitro (5–10 cm/s) and to be capable of destroying cells upon impact [79, 80]. However, in vivo, this ‘bubble bullet’ effect does not appear to be significant, possibly because a very high bubble:cell ratio is required [81 ]or because the presence of carbon dioxide in the blood has a damping effect upon bubble activity [74].…”
Section: Microbubble Phenomena In Therapeutic Applications: Physical mentioning
confidence: 99%